A Transplant-Inclusive Value-Based Kidney Care Payment Model - Benjamin E. Hippen; George M. Hart; Franklin W. Maddux (Kidney International Reports)
In the United States, kidney care payment models are migrating toward value-based care (VBC) models incentivizing quality of care at lower cost. Current kidney VBC models will continue through 2026. We propose a future transplant-inclusive VBC (TIVBC) model designed to supplement current models focusing on patients with advanced chronic kidney disease (CKD) and end-stage kidney disease (ESKD). The proposed TIVBC is structured as an episode-of-care model with risk-based reimbursement for “referral/evaluation/waitlisting” (REW, referencing kidney transplantation), “primary hospitalization to 180 days posttransplant,” and “long-term graft survival.” Challenges around organ acquisition costs, adjustments to quality metrics, and potential criticisms of the proposed model are discussed. We propose next steps in risk-adjustment and cost-prediction to develop as an end-to-end, TIVBC model.